Systematic Review of Meta-Analyses: Exercise Effects on Depression in Children and Adolescents - Wegner, Mirko; Amatriain-Fernández, Sandra; Kaulitzky, Andrea; Murillo-Rodriguez, Eric; Machado, Sergio; Budde, Henning (Frontiers in Psychiatry, 2020)
Background: Depression is a common threat to children and adolescents in terms of affecting psychosocial development and increasing their risk of suicide. Apart from conventional treatments for depression, physical exercise has become a promising alternative. This paper aims to systematically review the existing meta-analyses that focus on the impact of physical exercise on clinical and non-clinical depression in children and adolescents. Methods: A systematic literature search was conducted using PsycINFO, PsycARTICLES, MedLine, PubMed and hand searching. Risk of bias analysis, effect sizes calculations, and evaluation of the methodological characteristics (AMSTAR 2) were carried out. Results: Four meta-analyses met the inclusion criteria. After analysing the overlap, the total sample contained 30 single studies (mostly including gender mixed samples) and 2,110 participants (age range 5-20 years). The medium duration of the interventions was 11.5 weeks. The sessions had a medium length of 41 minutes, and the frequency of implementation was 3 sessions per week. The most implemented intervention type was aerobic exercise, while control groups mainly continued with their regular routine, among other related options. The overall mean effect of physical exercise on depression was medium (d = -0.50). The additional analysis in clinically depressed samples documented a small to medium mean effect (d = -0.48) in favour of the intervention. Conclusion: The small to medium but consistently positive effects that were found in the present study place physical exercise as a promising and helpful alternative for children and adolescents with clinical and non-clinical depression. The limited literature focused on children and adolescents in comparison with adult samples points to the need for further research.